Nutritional status in patients admitted to pediatric intensive care unit and its corelation with outcome - Patel, Maitri; Badhiye, Ankita; Chanpura, Vaishali; Patel, Bhargav (International Journal of Contemporary Pediatrics, 2024)
Background: The incidence of malnutrition in children admitted to pediatric intensive care unit (PICU), has always been significant. In addition, nutritional status of critically ill children deteriorates further during their PICU stay and may have negative effect on patients` outcome. This study aims to determine the critically ill children, to analyse and document its impact on outcome and to survey current nutritional practices and support in PICU. Methods: This was a prospective observational study done over a period of 10 months on critically ill patients admitted in PICU of department of pediatrics at Baroda medical college and Sir Sayajirao Gaekwad hospital, Vadodara. Results: Total of 350 patients admitted in PICU of S. S. G. hospital, Vadodara were enrolled in the study. Malnutrition was higher in age 6-60-month age group (57%) of patients admitted in PICU, 81% of severe acute malnutrition patients required mechanical ventilation and 19% required HFNC support, there was statistically significant difference in mortality (51.1%) of SAM patients as compared to normal patients. Conclusions: Malnutrition is one of the leading causes of mortality in patients admitted to PICU, with more complications with prolonged ventilator support, longer duration of stay in PICU.